Governance of Enterprise IT based on COBIT 5 - A Management Guide - Harmer, Geoff (IT Governance Publishing, 2018)
Written for IT service managers, consultants and other practitioners in IT governance, risk and compliance, this practical book discusses all the key concepts of COBIT®5, and explains how to direct the governance of enterprise IT (GEIT) using the COBIT®5 framework.